2005
DOI: 10.1056/nejmoa050518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening and Adjuvant Therapy on Mortality from Breast Cancer

Abstract: Seven statistical models showed that both screening mammography and treatment have helped reduce the rate of death from breast cancer in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,083
2
41

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,137 publications
(1,151 citation statements)
references
References 20 publications
25
1,083
2
41
Order By: Relevance
“…Breast cancer patients overexpressed with HER2 are associated with poor prognosis 22. HER2‐targeted therapy for HER2‐positive breast cancer patients has dramatically improved the survival rate and reduced mortality in recent history 23. HER2 gene amplification was first associated with worse clinical outcomes in the late 1980s by Slamon et al, and the following serious of studies revealed that residents at Asian‐Pacific areas were with high occurrence rate to be diagnosed with HER2‐positive status with a poorer diagnosis in comparison with other regions 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients overexpressed with HER2 are associated with poor prognosis 22. HER2‐targeted therapy for HER2‐positive breast cancer patients has dramatically improved the survival rate and reduced mortality in recent history 23. HER2 gene amplification was first associated with worse clinical outcomes in the late 1980s by Slamon et al, and the following serious of studies revealed that residents at Asian‐Pacific areas were with high occurrence rate to be diagnosed with HER2‐positive status with a poorer diagnosis in comparison with other regions 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…Screening mammography is currently the most effective way to detect breast abnormalities and has led to an estimated 10-25 % mortality reduction from breast cancer [1,2]. Even as mammography use has reached a plateau in recent years [3], mammography usage varies by state [4] and a significant proportion of women are not up-to-date with screening, especially low-income women, those who are uninsured [5,6] and those without usual source of care [7].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer mortality decreased in the US in 2000 for the first time [174], which is partly attributable to improvements in systemic therapy [175]. The progress has been incremental, with each new therapeutic intervention applied to the entire population, including individuals who may have been adequately treated with minimal or no systemic adjuvant therapy.…”
Section: Resultsmentioning
confidence: 99%